Activities of Daily Living and Associated Costs in the Most Widespread Neurodegenerative Diseases: A Systematic Review - Maresova, Petra; Hruska, Jan; Klimova, Blanka; Barakovic, Sabina; Krejcar, Ondrej (Clinical interventions in aging, 2020)
Nowadays, the population is rapidly ageing because of increasing life expectancy and decreasing birth rates. Thus, the purpose of this systematic review is to prepare a comprehensive overview which identifies the activities of daily living (ADLs) that are gradually reduced among patients with dementia, as well as explore the therapies applied in relation to dementia and how they effectively improve the quality of life (QoL) of patients and caregivers. Furthermore, we aim to summarise the ADL activities influenced by therapies and examine the treatment costs and care for patients so that recommendations for research and development (R&D) can be made to improve both the QoL of people with dementia and cost-saving measures. The research focuses on four selected neurodegenerative diseases: Alzheimer, Parkinson, vascular dementia, and amyotrophic lateral sclerosis. Therefore, the peer-reviewed English written articles from 2014 to 2019 were searched between September 1 and December 13, 2019. Twenty-seven papers were included in the analysis. The results show that essential assistance occurs in connection with activities: eating, drinking, dressing, bathing, personal hygiene, use of the toilet, and transport. By contrast, shopping or cleaning is not addressed as much. A lower ability to take care of oneself is connected with poor patient health and higher social care costs because the patient requires care from external sources, such as home aid or nurse visits. The challenge that remains is to shift new knowledge from scientific disciplines and connect it with the needs of patients to remove legitimate barriers and increase the acceptance of new solutions by popularisation. Additionally, regarding the burden on caregivers, it would be appropriate to promote this area of education and employment so that family members can use formal caregivers, ensuring them free time and much-needed rest.
Keywords: costs; Male; kvalita života; Quality of Life; neurodegenerative diseases; Neurodegenerative Diseases; náklady na zdravotní péči; Aged; činnosti denního života; mužské pohlaví; senioři; quality of life; neurodegenerativní nemoci; senioři nad 80 let; activities of daily living; lidé; ženské pohlaví; Humans; Health Care Costs; Aged, 80 and over; Activities of Daily Living; Female; lidé středního věku; Middle Aged